Characteristics Associated With Growth Differentiation Factor 15 in Heart Failure With Preserved Ejection Fraction and the Impact of Pirfenidone - Gavin A. Lewis; Anna Rosala‐Hallas; Susanna Dodd; Erik B. Schelbert; Simon G. Williams; Colin Cunnington; Theresa McDonagh; Christopher A. Miller (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Growth differentiation factor 15 (GDF‐15) is elevated in heart failure with preserved ejection fraction and is associated with adverse outcome, but its relationship with myocardial fibrosis and other characteristics remains unclear. We sought to evaluate the effect of pirfenidone, a novel antifibrotic agent, on GDF‐15 in heart failure with preserved ejection fraction and identify characteristics that associate with GDF‐15 and with change in GDF‐15 over 1 year. Methods and Results Among patients enrolled (n=107) in the PIROUETTE (Pirfenidone in Patients With Heart Failure and Preserved Left Ventricular Ejection Fraction) trial, GDF‐15 was measured at baseline and at prespecified time points in patients randomized (n=94) to pirfenidone or placebo. The response of GDF‐15 to pirfenidone and the association with baseline patient characteristics were evaluated. Pirfenidone had no impact on circulating GDF‐15 at any time point during the 52‐week trial period. In multivariable analysis, male sex, diabetes, higher circulating levels of N‐terminal pro‐B‐type natriuretic peptide, lower renal function, and shorter 6‐minute walk test distance at baseline were associated with baseline log–GDF‐15. Impaired global longitudinal strain at baseline was the strongest predictor of increased GDF‐15 over 52 weeks. Conclusions In patients with heart failure with preserved ejection fraction, circulating levels of GDF‐15 were unaffected by treatment with pirfenidone and do not appear to be determined by myocardial fibrosis. Circulating GDF‐15 was associated with a spectrum of important heart failure characteristics and it may represent a marker of overall physiological disruption. Registration URL: https://clinicaltrials.gov/ct2/show/NCT02932566; Unique identifier: NCT02932566.